The Application of 3D Imaging as an Appropriate Method of Wildlife Craniometry: Evaluation of Accuracy and Measurement Efficiency - Košinová, Klára; Turek, Jiří; Cukor, Jan; Linda, Rostislav; Häckel, Martin; Hart, Vlastimil (Animals, 2022)
The suitability of CT and 3D scanners for craniometric proposes was tested using digital calipers when determining linear measurements, and a measuring cylinder was used for the accuracy of 3D printing of deer antlers obtained by the CT and 3D scanners. The resolution of digitized objects from a 3D scanner ranged from 0.008 mm to 0.122 mm. For mandibular dimensions, a positive deviation (p < 0.01) from the primary control measurement was recorded. The average antler volume measured with the cylinder was 60.47 cm3 at the first measurement, in the case of the CT scanner 61.62 cm3 and for the 3D scanner 64.76 cm3—both technologies exhibit a positive deviation from the primary measurement. Precise sensing and measurements can be used to evaluate the quality and evolution of wildlife populations, create digital museum collections, or to examine in detail certain traits such as antler and horn development or dentition.
Keywords: mandible; 3D scanner; reproducibility of results; geometric morphometric; CT; antlers